Energy-Efficient Uniquely-Decomposable Multilayer Modulation for Peak-Limited Broadcast DTP Channels - Ling-Han Si-Ma; Hong-Yi Yu; Jian Zhang (IEEE Photonics Journal)
A multilayer modulation for peak-limited broadcast Poisson channel is designed and consists of three key elements: the transmitted symbol set, the users’ data space, and the data-to-symbol mapping. For energy-efficiency, the transmitted symbols are modulated by the square pulse amplitude modulation. Meanwhile, a concept of uniquely decomposable constellation group is developed to resist the nonnegative multiuser interference in power domain. Combining this concept and the transmitted symbol structure, we design the users’ data space and the data-to-symbol mapping such that, for this mapping, the transmitted symbol can be uniquely decomposed as elements of users’ data space. The above described structure of the multilayer modulation enables not only efficient demodulation of the transmitted symbol from Poisson noisy received signal but also data decoding for each user from the estimation of the transmitted symbol. Extensive computer simulations indicate that the multilayer modulation not only has better overall error performance than the currently available time-sharing protocol, but also allows us to flexibly assign different priority. Additionally, a low-complexity receiver is established for the proposed multilayer modulation, whose error performance gradually approximates that of maximum likelihood receiver with the increment of optical power.